Active magnetic decoupling for improving the performance of integrated LCL-filters in grid-connected converters - Li, Xiaoqiang (2019)
Magnetically integrating converter-side and grid-side inductors is an effective way to reduce the volume and weight of LCL filters. However, the inevitable magnetic coupling between the two coils weakens the high order harmonic attenuation ability of LCL filters. In this paper, an active magnetic decoupling method is proposed to tackle this issue, and the basic operation principle is to counteract the coupling inductor in the filter capacitor branch by constructing a decoupling inductor. A step-by-step design guidance of integrated LCL filters with the proposed magnetic decoupling method is presented in detail, and it is also found that a further volume reduction of magnetic cores can be achieved compared to the existing passive decoupling method. Experimental results finally verify the effectiveness of the proposed method.